Palm oil as a renewable raw material in the synthesis of new polymeric materials through the epoxy fusion process - A. Sienkiewicz; P. Czub; A. Milo (eXPRESS Polymer Letters, 2021)
The presented research shows the results of the investigations on the synthesis of polymeric materials through the fusion reaction of modified palm oil derivatives. First, raw palm oil was subjected to epoxidation. In order to determine the best reaction conditions, the process was conducted under four different conditions. In the next stage, the polyaddition products were obtained by the reaction of epoxidized palm oil (EOP) and bisphenol A (BPA), through the epoxy fusion process. On the basis of the performed studies, using both analysis of the content of functional groups, as well as data obtained from FT-IR, GPC, 1H NMR and 13C NMR analyses of the chemical structure of all obtained palm oil derivatives was determined. It was found that during the polyaddition process, after the reaction of the oxirane group of EOP with the hydroxyl group of BPA, a subsequent reaction occurred, involving the reaction of a free phenolic group with the following macromolecule of modified oil. Finally, obtained bio-polyaddition products were used: (1) to obtain ‘stand-alone’ epoxy-polyurethane materials and (2) as modifiers of a commercial bisphenol A-based low molecular weight epoxy resin.